2008
DOI: 10.1523/jneurosci.1006-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Neuronal Death in Hippocampus Requires the Microglial CD11b Integrin and DAP12 Immunoreceptor

Abstract: In several brain regions, microglia actively promote neuronal apoptosis during development. However, molecular actors leading microglia to trigger death remain mostly unknown. Here, we show that, in the developing hippocampus, apoptotic neurons are contacted by microglia expressing both the integrin CD11b and the immunoreceptor DAP12. We demonstrate that developmental apoptosis decreases in mice deficient for CD11b or DAP12. In addition, function-blocking antibodies directed against CD11b decrease neuronal dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
299
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(310 citation statements)
references
References 35 publications
10
299
0
1
Order By: Relevance
“…This type of scheme is supported by the findings that low levels of caspase activation in neurons can be reversible (45), and that phagocytosis actively contributes to developmental programmed cell death in Caenorhabditis elegans when caspase-3 activation is weak (46,47). Furthermore, knockout of the putative PS receptor in mice prevents developmental neuronal loss leading to pathologically enlarged brains (48), and microglia are known to mediate the loss of neurons in the developing mouse cerebellum and hippocampus (49,50). These findings are suggestive of microglia or microglial phagocytosis contributing to neuronal death in mammals, and using immortalized cell lines, a recent study has reported the phagocytosis of The Journal of Immunology"normal" neurons by LPS-or amyloid-activated microglia (51).…”
Section: Discussionmentioning
confidence: 86%
“…This type of scheme is supported by the findings that low levels of caspase activation in neurons can be reversible (45), and that phagocytosis actively contributes to developmental programmed cell death in Caenorhabditis elegans when caspase-3 activation is weak (46,47). Furthermore, knockout of the putative PS receptor in mice prevents developmental neuronal loss leading to pathologically enlarged brains (48), and microglia are known to mediate the loss of neurons in the developing mouse cerebellum and hippocampus (49,50). These findings are suggestive of microglia or microglial phagocytosis contributing to neuronal death in mammals, and using immortalized cell lines, a recent study has reported the phagocytosis of The Journal of Immunology"normal" neurons by LPS-or amyloid-activated microglia (51).…”
Section: Discussionmentioning
confidence: 86%
“…It is therefore possible that microglial Nox1 contributes to an immune defense against microorganisms that threaten the CNS (Rock et al, 2004). The cytotoxic activity of phagosomal O 2 ⅐Ϫ also participates in normal development, where engulfing microglia cause neuronal apoptosis (Marín-Teva et al, 2004;Wakselman et al, 2008). Our study shows that Nox1, expressed in microglia in the developing brain, might play a key role in this mechanism of neuronal death.…”
mentioning
confidence: 72%
“…Microglia are found in close proximity to apoptotic neurons in the developing brain, where they remove apoptotic debris (43)(44)(45), as well as induce programmed cell death. Microglia induce apoptosis in Purkinje cells of the cerebellum, but also in other brain regions including hippocampus, via release of superoxide ion, similar to the respiratory bursts seen in neutrophils (46)(47)(48). Release of superoxide ion is induced by the integrin CD11b and the immune receptor DNAX activation protein of 12 kDa (DAP12) after microglial interaction with the target neuron (48).…”
Section: Microglia In Steady Statementioning
confidence: 95%